Effect of Western and Korean Medicine Combination Treatment on Physical Activity in Elderly Arthropathy Patients - Tae-Hyeon Lee; Su-Hyun Kwon; Ji-A Ryu; Sang-Ji Han; Il-Su Park; Chan-Young Kwon (Journal of Pharmacopuncture)
Objectives: This study analyzed data from the Korean Health Panel Survey (2015-2018) to determine the effects of combined Western and Korean medicine treatments on physical activity (PA) in elderly patients with arthropathy. PA was assessed using the total PA score from the International Physical Activity Questionnaire. Methods: This study included 2,518 unique elderly patients, generating 8,003 annual outpatient service cases over the 4-year period. Of these annual cases, 5,384 cases (67.3%) were classified as Western medicine (WM) treatment alone, and 2,619 cases (32.7%) were classified as combined treatment (WM&KM). Descriptive statistical analysis was performed to identify changes in PA in the WM and WM&KM groups and KM medical utilization in the WM&KM group. Generalized estimating equations (GEE) with control variables were used to determine the effects of the WM&KM combination treatments on PA. Results: Both the WM and WM&KM groups showed a decline in PA over four years. However, the rate of PA decline was lower in the WM&KM group compared to the WM group. In the WM&KM group, acupuncture (50.42%) was the most utilized KM modality, followed by physiotherapy (44.17%), herbal medicine (2.51%), moxibustion (0.84%), and cupping (0.69%). The GEE analysis revealed that the total physical activity of the WM&KM group was 84.29 significantly higher than the WM group (p < 0.001). Conclusion: While PA decreased continuously in elderly patients with arthropathy, the WM&KM group exhibited a slower decline, suggesting the effectiveness of KM treatment in mitigating PA reduction. To slow the progression of arthropathy and alleviate pain, it is crucial to provide comprehensive and proactive medical services through collaborative efforts between WM and KM.